Police encounters with African youth in New Zealand – the impact on the youth, family, and community. Issue 2 (10th April 2017) - Nakhid, Camille
Abstract : Purpose: The purpose of this paper is to look at the impact of police encounters with young African New Zealanders (referred to in this paper as African youth) on the youth themselves, their family and their community. Design/methodology/approach: While much of the existing literature takes a quantitative approach to research the impact of police behaviours on community trust, this paper seeks to gain a qualitative understanding of how the African youth and their community in Aotearoa (Māori word for New Zealand) New Zealand are impacted by encounters with the police. Findings: Qualitative data shared by 32 African youth living in Auckland showed that police encounters had left the youth emotionally fearful and wary of any future contact with the police, and had negatively affected their employment opportunities. The family and community were unwilling to seek assistance from the police in times of need with members becoming depressed and withdrawing from community contact because of the shame brought on by these encounters. Research limitations/implications: The ability to generalize the findings is limited as participants were recruited primarily through African youth themselves, African social and community organizations and youth workers. Social implications: It is important to understand the impact that encounters with the police have on African youth in New Zealand because of the rate of increase in the numbers of African youth in the country, and the need for young people and their communities to feel safe with those legitimately responsible for their safety. Originality/value: There is almost no literature on the experiences of African youth with the police in New Zealand and none on how these experiences impact on the youth, their family and community.